A Pipeline for the Development of Microsatellite Markers using Next Generation Sequencing Data - Antunes, Adriana M.; Stival, Júlio G. N.; Targueta, Cíntia Pelegrineti; de Campos Telles, Mariana Pires; Soares, Thannya Nascimento (Current Genomics, 2022)
Background: Also known as Simple Sequence Repetitions (SSRs), microsatellites are profoundly informative molecular markers and powerful tools in genetics and ecology studies on plants. Objective: This research presents a workflow for developing microsatellite markers using genome skimming. Methods: The pipeline was proposed in several stages that must be performed sequentially: obtaining DNA sequences, identifying microsatellite regions, designing primers, and selecting candidate microsatellite regions to develop the markers. Our pipeline efficiency was analyzed using Illumina sequencing data from the non-model tree species Pterodon emarginatus Vog. Results: The pipeline revealed 4,382 microsatellite regions and drew 7,411 pairs of primers for P. emarginatus. However, a much larger number of microsatellite regions with the potential to develop markers were discovered from our pipeline. We selected 50 microsatellite regions with high potential for developing markers and organized 29 microsatellite regions in sets for multiplex PCR. Conclusion: The proposed pipeline is a powerful tool for fast and efficient development of microsatellite markers on a large scale in several species, especially nonmodel plant species.
Keywords: microsatellite markers